Apt Perception, Aesthetic Engagement, and Curatorial Practices - Emine Hande Tuna; Octavian Ion (Estetika, 2024)
This paper applies the account developed by Susanna Siegel in The Rationality of Perception to aesthetic cases and explores the implications of such an account for aesthetic engagement as well as curatorial and exhibitionary practices. It argues that one’s prior outlook – expertise, beliefs, desires, fears, preferences, attitudes – can have both aesthetically good and bad influences on perceptual experiences, just as it can have both epistemically good and bad influences. Analysing these bad influences in cases of ‘hijacked’ aesthetic perception will reveal that, unless we recognize that our perception of high-level and low-level aesthetically relevant properties is norm-governed, we will be at a loss to explain what goes wrong in these cases. Just as perception can be rational or irrational, so too can it be apt or inapt.